Pasado, presente, hegemonía - Pato, Cecilia (International Gramsci Journal, 2023)
Starting from an analytical perspective combining political theory and intellectual history, the present contribution outlines the Gramscian experience in Latin America, devoting particular attention to the two-stage (1963-65 and 1973) reception and interpretation of Gramscian political theory by the review Pasado y Presente. Taking the review as a space for political and cultural intervention, the essay reconstructs the influence it had on the legacy of Gramscian theory, with special regard to the reflections on the concept of hegemony proposed by the two people, José Aricó and Juan Antonio Portantiero, with whom the review is most associated.